DEVELOPMENT OF INQUIRY-BASED BIOLOGY MODULE TO IMPROVE LEARNING AT SMA NEGERI 1 SAKRA TIMUR - nikmah (Innovative Pedagogy and Education Studies, 2024)
This study developed an inquiry-based biology module to enhance student engagement and conceptual understanding in line with the Merdeka Curriculum. Conducted at SMA Negeri 1 Sakra Timur, it involved 26 students in the experimental group and 24 in the control group, using the Research and Development (R&D) method based on a modified Borg and Gall model. The module followed an Inquiry-Based on Interactive Demonstration approach with five stages: observation, manipulation, generalization, verification, and application. Results showed significant improvements in cognitive (85.89 vs. 79.92), affective (89.74 vs. 73.13), and psychomotor (89.48 vs. 30.84) aspects compared to conventional methods. The module effectively enhanced critical thinking, motivation, and practical skills, supporting 21st-century competencies. Despite challenges like time constraints and teacher training needs, proper planning can ensure success. This inquiry-based module is recommended for broader adoption to foster interactive and student-centered learning.